Mispricing in CNX Nifty Futures: An Empirical Investigation. (December 2014) - Nandan, Tanuj; Agrawal, Puja; Bhargava, Shachi
Derivatives markets have witnessed considerable growth since their inception at Indian stock exchanges. In the present study, we aim to assess the pricing efficiency of the CNX Nifty index futures. We compare the theoretical cost of carry price with the corresponding observed prices for the period January 2003 to December 2012. In an efficient market, these two are expected not to differ, since such a deviation could lead to riskless arbitrage opportunities. Non-parametric tests are employed to test the statistical significance of our results. We report that the CNX Nifty futures are frequently underpriced, possibly due to short-sales restrictions. There are instances of overpricing, too, but the frequency and magnitude of such scenarios are fewer. We find significant differences in the behaviour of mispricing between the instances of negative/positive basis. Similarly, there appears to be a significant difference between mispricing series with changing days to expiry. These findings can have important implications, which are presented in the conclusion along with an outline of future prospects for research.